Postcards from paradise [compact disc] - Starr, Ringo (UMe, 2015)
Just before his solo induction into the Rock and Roll Hall of Fame, Ringo Starr releases his first new studio album in three years. He is joined by several guests including Joe Walsh, Richard Marx, Peter Frampton, and more.